Innovative leadership of School Administrators in Schools of Education Sandbox, Pattani Province - Mu'tasimbillah, Ni-ibnurowee; ยี่สุ่นทรง, อะห์มัด (Al-HIKMAH Journal, 2024)
This mixed-method study aims to investigate, compare, and study guidelines the innovative leadership of educational institution administrators in Schools of the Education Sandbox Initiative in Pattani Province. The quantitative component analyzes responses from a sample of 317 individuals using surveys, with data analyzed through frequency distributions, percentages, means, standard deviations, t-tests, and one-way ANOVA. The qualitative component involves in-depth group discussions with four school administrators in the Education Sandbox Initiative in Pattani Province and one university lecturer. Collecting data by analyzing data using methods of description, synthesis, interpretation and drawing conclusions from various data. The findings of this study revealed that 1) both overall and in specific aspects, is at a high level of innovative leadership of school administrators in the Education Sandbox initiative, Pattani Province. 2) Comparative results of innovative leadership when classified by gender and work experience, with statistically significant differences in both overall at the .05 level and classified according to the size of the overall educational institution were significantly different at the .01 level. And 3) Guidelines for developing innovative leadership seem that school administrators should adjust their vision and always ready to deal with change to present creative ideas, think outside the box, and have flexible attitudes and ideas, including with continuous monitoring and development of personnel and a network of cooperation from all sectors has been created.